The "state of the art" of teaching in Rural Extension in Brazil - Daiane Loreto de Vargas; Laila Mayara Drebes (Universidade Federal do Norte do Tocantins, 2022)
This article aims to carry out an analysis of the "state of the art" of teaching in Rural Extension in Brazil, considering the panorama of the offer of the discipline, current academic trends and the profile of teachers, comparing data from surveys carried out in 2008, 2010 and 2022 based on the Forum that brings together Rural Extension teachers. The research is qualitative-quantitative in nature and at a descriptive level. Data from 2008 and 2010, published in research reports, serve as a comparison for data collected through an electronic form with 49 Rural Extension teachers from a universe of 136 teachers from all regions of the country. The results point to evidence in the discipline such as: trend of change in nomenclature; theoretical and practical offer; taught as compulsory in courses in Agricultural Sciences and as optional in some courses in Human and Social Sciences; offered in the final semesters of graduation. The profile of the professors who teach the discipline can be summarized as: experienced (majority with more than 5 years of teaching experience), qualified (professors with a PhD), active in addition to teaching, also in research and university extension, articulated with a diversity of issues of interest to Rural Extension and increasingly integrated into postgraduate.